2018
DOI: 10.1371/journal.pone.0203544
|View full text |Cite
|
Sign up to set email alerts
|

Reality check of using the surgical safety checklist: A qualitative study to observe application errors during snapshot audits

Abstract: BackgroundThe WHO Surgical Safety Checklist (SSC) was established to address important safety issues and to reduce the number of surgical deaths. So far, numerous reports have demonstrated sub-optimal implementation of the SSC in practice and limited improvements in patient outcomes. Therefore, the aim of this study was to audit the SSC-practice in a real-world setting in a university hospital setting.MethodsFrom 2015 to 2016, independent observers performed snapshot audits in operating theatres and shadowed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
(38 reference statements)
0
22
0
3
Order By: Relevance
“…Lediglich die Gruppe der nicht zertifizierten Zentren bleibt im Kontrolljahr mit 77,9 % hinter dem Vergleichswert der Literatur zurück. Sendlhofer et al (2018) sieht den Grund für die hohen Akzeptanzwerte des »Sign-In« darin, dass hier nur eine Berufsgruppe, die Anästhesie, das Verfahren leitet und im Gegensatz zu den weiteren Parametern (»Team-Time-Out«, »Sign-Out«) keine Interaktion mit weiteren Systempartnern erforderlich ist [29]. Es überrascht in dieser Studie, dass das monodisziplinär zu verantwortende »Sign-In«, im Indexjahr zwischen den zertifizierten und den nicht zertifizierten Zentren ein signifikant unterschiedliches Resultat liefert.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Lediglich die Gruppe der nicht zertifizierten Zentren bleibt im Kontrolljahr mit 77,9 % hinter dem Vergleichswert der Literatur zurück. Sendlhofer et al (2018) sieht den Grund für die hohen Akzeptanzwerte des »Sign-In« darin, dass hier nur eine Berufsgruppe, die Anästhesie, das Verfahren leitet und im Gegensatz zu den weiteren Parametern (»Team-Time-Out«, »Sign-Out«) keine Interaktion mit weiteren Systempartnern erforderlich ist [29]. Es überrascht in dieser Studie, dass das monodisziplinär zu verantwortende »Sign-In«, im Indexjahr zwischen den zertifizierten und den nicht zertifizierten Zentren ein signifikant unterschiedliches Resultat liefert.…”
Section: Diskussionunclassified
“…Die unangekündigte prospektive quantitative Evaluation der OP-Checklisten ist ein probates Mittel für eine Einordnung des Nutzungsverhaltens [29]. Die von uns beobachtete Diskrepanz zwischen Compliance-Raten von »zertifizierten Zentren« (Erst-oder Re-Audit) vs. »nicht zertifizierte Zentren« ist besonders beachtenswert.…”
Section: Diskussionunclassified
“…When implemented ineffectively, the use of checklists have failed to demonstrate clinical improvements (Sendlhofer and others 2018). Successes and failures in implementation reflect the complex challenges in patient safety and quality improvement (Catchpole and Russ 2015).…”
Section: Barriers and Facilitators To Implementationmentioning
confidence: 99%
“…This was confirmed in a study using snapshot audits that found team timeout errors in 40 to 60 percent of cases. [11] Consequently, there remains considerable uncertainty regarding the quality and performance of the surgical checklist timeout procedure, including its true efficacy for picking up critical . CC-BY-NC-ND 4.0 International license It is made available under a perpetuity.…”
Section: Introductionmentioning
confidence: 99%
“…This was confirmed in a study using snapshot audits that found team timeout errors in 40 to 60 percent of cases. [11] Consequently, there remains considerable uncertainty regarding the quality and performance of the surgical checklist timeout procedure, including its true efficacy for picking up critical 4 mistakes. [12] For checklists to be effective, however, it is not only important that the listed items be mentioned, but also that potential errors be picked up by the team.…”
Section: Introductionmentioning
confidence: 99%